Tracing an Unyielding Work Compulsion: A Moderated Mediation Model of Abusive Supervision and Compulsory Citizenship Behavior - Baig, Ali T.; Riaz, Zahid (Frontiers in Psychology, 2021)
We conceptualize and examine an integrated model of compulsory citizenship behavior in the employees of the insurance sector. For this purpose, direct and indirect influence of job demands (active-aggressive and passive-aggressive abusive supervisions) is examined on the compulsory citizenship behavior. In so doing, the relevance of perceived support of coworkers as a job resource and emotional exhaustion as an underlying mechanism is investigated. Data were collected from 205 managerial level employees working in the insurance sector of a developing economy. Both aspects of abusive supervision have both direct and indirect effects through emotional exhaustion on compulsory citizenship behavior. Active-aggressive abusive supervision, coupled with low perceived coworkers’ support influences emotional exhaustion that culminates in increased compulsory citizenship behavior of employees. Interestingly, when perceived support of coworkers is high, the indirect link between active aggressive abusive supervision and compulsory citizenship behavior through emotional exhaustion decreases. For human resource managers, these findings imply that the proper background checks should be made before the recruitment so that employees with troubled past or tending to exhibit aggression can be screened. For line managers, these findings imply that coworkers can play a major role in curbing the compulsory citizenship behavior. Thus, managers should foster such organizational practices that can develop mutual trust and stronger relationship among coworkers so that coworkers can become the perfect source of psychological support.